KORELASI PERSEPSI SISWA TENTANG KOMPETENSI PEDAGOGIK GURU DENGAN HASIL BELAJAR SISWA PADA PEMBELAJARAN PAI DI SMP QUR’AN AL-ZAMRIYAH KABUPATEN LIMA PULUH KOTA - Zakiyatul Salma; Zulfani Sesmiarni; Supratman Zakir; Junaidi Junaidi (KOLONI, 2022)
This research is motivated by the competence of the teacher to form different perceptions for students, so that the perceptions given in the learning process, especially pedagogic competencies, affect learning outcomes. The purpose of this study was to find out more about students' perceptions of teacher pedagogic competence and student learning outcomes in PAI learning and to find out the correlation between students' perceptions of teacher pedagogical competencies and student learning outcomes in PAI learning at SMP Qur'an Al-Zamriyah Lima District. Twenty Cities.This type of research is correlational quantitative research, which is a research that investigates whether there is a correlation between two or more variables. The population in this study were students of the Qur'an Al-Zamriyah Junior High School, Lima Puluh Kota Regency, which amounted to 113 people with a research sample of 53 people consisting of class VII, VIII and class IX students. The data collection technique used was a questionnaire/questionnaire for students' perceptions of the teacher's pedagogic competence and documentation for student learning outcomes. The data analysis technique that the author uses is descriptive data analysis, prerequisite analysis test in the form of data normality test and linearity test. Then test the hypothesis using the Product Moment Correlation formula.The results showed that students' perceptions of the teacher's pedagogic competence were included in the "good" category, with the percentage of achievement being 84.56%. Meanwhile, for student learning outcomes in PAI learning are included in the "good enough" category based on their position in the table list of categories of student learning outcomes with an average (mean) of 88.19. The results of this study also show that there is a correlation between students' perceptions of teacher pedagogical competence and student learning outcomes in PAI learning at SMP Qur'an Al-Zamriyah, Lima Puluh Kota Regency with a correlation coefficient value of 0.468 with a "strong enough" level of relationship. Keywords: Perception, Pedagogic Competence, Learning Outcomes